2021
DOI: 10.1167/tvst.10.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Retinal Vascular Histology to Validate an Optical Coherence Tomography Angiography Technique

Abstract: To determine the fidelity of optical coherence tomography angiography (OCTA) techniques by direct comparison of the retinal capillary network images obtained from the same region as imaged by OCTA and high-resolution confocal microscope.Method: Ten porcine eyes were perfused with red blood cells for OCTA image acquisition from the area centralis and then perfusion-fixed, and the vessels were labeled for confocal imaging. Two approaches involving post-processing of two-dimensional projection images and vessel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
3
14
0
Order By: Relevance
“…We also found that there was an underrepresentation of small calibre vessels on OCTA, especially those located in highly reflective layers (ICP). These findings have also been reported when evaluating OCTA in ex vivo pig eyes (Yu et al, 2021). When compared to images acquired at the same locations by confocal microscopy/IHC, our results suggest that OCTA is a valuable technique for visualising and quantifying retinal vasculature in dogs, especially for analysis of VD in the DCP.…”
Section: Optical Coherence Tomography Angiography Is a Valid Methods For Non-invasive In Vivo Characterisation Of Retinal Vascular Networsupporting
confidence: 81%
See 1 more Smart Citation
“…We also found that there was an underrepresentation of small calibre vessels on OCTA, especially those located in highly reflective layers (ICP). These findings have also been reported when evaluating OCTA in ex vivo pig eyes (Yu et al, 2021). When compared to images acquired at the same locations by confocal microscopy/IHC, our results suggest that OCTA is a valuable technique for visualising and quantifying retinal vasculature in dogs, especially for analysis of VD in the DCP.…”
Section: Optical Coherence Tomography Angiography Is a Valid Methods For Non-invasive In Vivo Characterisation Of Retinal Vascular Networsupporting
confidence: 81%
“…However, the absolute values can vary widely between studies and there is a need for validation of novel OCTA-based approaches in canine retinas. Currently, the most recognized method of validating OCTA images is via direct comparison with retinal wholemounts processed for detection of the retinal vasculature by immunohistochemistry (IHC) ( Yu et al, 2021 ). Ultimately, in order to be considered a reliable imaging technique, OCTA must recognize the majority of the vessels that are visualized by IHC.…”
Section: Introductionmentioning
confidence: 99%
“…Capillary density extracted from OCTA slabs is generally calculated by dividing the surface area of automatically or manually traced capillaries by the area of the retina sampled. Comparisons between densities extracted from histology and OCTA using perfused human donor eyes (An et al, 2018;Balaratnasingam et al, 2018) and animal eyes (Yu et al, 2021) indicate that OCTA provides a good representation of large retinal vessels but does not visualize all retinal capillaries. Estimates of capillary density obtained from OCTA slabs range from 10 to 60% on average in similar regions of the retina (Coscas et al, 2016;Iafe et al, 2016;Garrity et al, 2017;Lavia et al, 2019).…”
Section: Retinal Vasculaturementioning
confidence: 99%
“…In these studies, a good representation of retinal vessels with larger caliber, but an under representation of microvessels smaller than 10 μm and branch points in all four retinal plexuses, particularly the intermediate capillary plexus, was observed. Also, the sensitivity to detect vessels was reduced with increasing retinal depth ( 103 ). A reason for weaker OCTA signals in vessels with a diameter under 100 μm could be a hemodynamic feature, called Fahraeus-Lindquist effect.…”
Section: Methods Of Measurementmentioning
confidence: 99%
“…A reason for weaker OCTA signals in vessels with a diameter under 100 μm could be a hemodynamic feature, called Fahraeus-Lindquist effect. It leads to a diameter-dependent decrease of hematocrit and effective blood viscosity, which means that there are less blood cells and larger plasma gaps in the smaller retinal capillaries ( 103 ). Moreover, the fact that the OCTA image signal is produced by red blood cell movement within the vascular lumen may also explain that the vessel diameter measured by OCTA does not exactly correspond to the actual size.…”
Section: Methods Of Measurementmentioning
confidence: 99%